Frontal lobe dysfunction in Alzheimer disease: Assessment and prognostic significance. - Collins, Barbara. (University of Ottawa (Canada), 1998)
The purpose of the present study was twofold: (1) to investigate whether degree of frontal lobe dysfunction predicts dementia progression in early Alzheimer disease (AD) and age associated memory impairment (AAMI); and (2) to investigate the validity mid potential utility of delayed alternation (DA) and delayed response (DR) paradigms, sensitive and specific markers of frontal lobe function in primates, as measures of frontal dysfunction in human patients with AD and AAMI. Subjects included 19 patients with early AD recruited from two local memory clinics and IS community-residing volunteers meeting National Institute of Mental Health diagnostic criteria for AAMI. Mental status tests and a functional rating scale were administered at intake to the study and again one year later and scores on these scales were used to calculate an index of mental status change. Memory Screening tests used in the diagnosis of AAMI were also readministered one year after intake to the study, thus permitting calculation of a memory change measure in the AAMI subgroup. At intake to the study, all subjects were also administered DA and DR tasks, clinical neuropsychological tests of frontal and parietal lobe functioning, and a SPECT (single photon emission computed tomography) brain scan. Contrary to prediction, frontal lobe functioning, whether assessed by means of clinical neuropsychological tests, regional cerebral blood flow, or experimental behavioural paradigm (DA and DR), did not predict mental status change in either the AD patients, the AAMI subjects, or the combined sample. However, performance on frontal neuropsychological tests did predict the degree of positive practice effect on memory retesting in the AAMI subjects. Parietal lobe functioning, as measured by both regional cerebral blood flow and neuropsychological testing was somewhat predictive of mental status change, with lower parietal perfusion associated with greater decline in mental status. Performance on the DA and DR tasks was not associated with frontal perfusion but did correlate with scores on frontal neuropsychological measures (more strongly than with scores on parietal neuropsychological measures). Some of the behavioural measures of executive functioning used in the current study, namely, the Colour-Form Sorting Test and the DA task, were found to be very specific markers of dementia (i.e., performance on these tasks was virtually never impaired in the nondemented subjects). These findings permit the following conclusions: (1) DA appears to be a valid measure of frontal lobe functioning in individuals with AAMI and early AD; (2) certain simple executive tasks, such as DA and the Colour-Form Sorting Test, may be worthwhile additions to dementia screening batteries which, for the most part, lack measures of executive functioning; (3) the ability of elderly adults to benefit from previous experience may depend on executive functioning and thus learning in this population may be enhanced by support of executive functioning; and (4) severity of parietal lobe dysfunction may predict dementia progression rate in early AD patients.
Keywords: Biology, Neuroscience.